Understanding the Factors Affecting Sustainable Energy Action Plan: A Case Study From the Covenant of Mayors Signatory Municipality in the Aegean Region of Turkey - Biresselioglu, Mehmet Efe; Demir, Muhittin Hakan (Frontiers in Psychology, 2021)
This study presents the case of a Metropolitan Municipality in the Aegean Region of Turkey, which undertook a series of initiatives to conduct projects on environmental protection and sustainability. This case study was conducted as two separate studies as a part of Horizon 2020 funded ECHOES project under Work Package 6, aiming to gain insight into the collective magnitudes of energy-related choices and behavior. The starting point of the process is marked, in 2015, by the municipality becoming a party to the Covenant of Mayors movement, joining around 8000 signatories from over 50 countries. In line with EU’s climate targets and associated energy-related policies, signatories of the Covenant of Mayors aim to decrease carbon emissions by 20% by 2020 and by 40% by 2030. In order to enhance the design and operationalization of policies for achieving these targets, each partner in the Covenant of Mayors is required to develop a Sustainable Energy Action Plan (SEAP). The SEAP is to be prepared within two years of becoming a party to the Covenant of Mayors, and involves action plans and projects in order to operationalize the strategies for achieving the associated targets. To this end, this study analyses the Metropolitan Municipality’s SEAP and its components, which include zero-emission public transportation project, transformation of existing buildings to a more energy efficient standard and related energy audit studies, a project for decreasing waiting periods in traffic via a Smart Traffic System, a pedestrianization project, and a project for increasing the use of geothermal energy for district heating. This study set out to identify the internal and external factors, as well as bottom-up and top-down mechanisms involved in various phases of the preparation and implementation of the SEAP. The research method was expert interviews, incorporating viewpoints and perceptions of stakeholders from different levels of the municipality. Among the key results are the understanding of roles of enthusiasts and frontrunners in such initiative, and importance of top management and central government support.